Effect of stand density, canopy leaf area index and growth variables on Dendrocalamus brandisii (Munro) Kurz litter production at Simao District of Yunnan Province, southwestern China - Tinsae Bahru; Yulong Ding (Global Ecology and Conservation, 2020)
Litterfall is the primary interface between the forest canopy and forest floor for efficient carbon and nutrient cycling. However, there is limited knowledge on factors that influence D. brandisii litter production and its seasonal dynamics. In this study, we investigated the relationship between stand density, canopy leaf area index (LAI) and growth variables in relation to litter production and its seasonal dynamics. In the 5-year-old D. brandisii plantation, three blocks were established and 72 litter traps were installed in the forest floor. Litter collection was conducted at the end of every season from June 2018 to May 2019. The relationship between litter production with climate variables further analyzed using 12 months weather data. On average, 207.23 ± 6.89 g m−2 y−1 D. brandisii annual litter production was recorded in the forest floor. Of this, the highest amount of litterfall (97.39 ± 4.62 g m−2 y−1) was obtained during warm and rainy summer season, followed by autumn (52.42 ± 2.43 g m−2 y−1). Higher stand density with larger canopy leaf area attributed to enhanced canopy LAI. Dense stands associated with closed canopy closure, by contrast, reduced culms diameter at breast height (DBH) size. This results in lower canopy LAI and hence reduced litter production in the forest floor. Alternatively, lower canopy leaf area compared to higher canopy spread area resulted in reduced canopy LAI (0.74 ± 0.09 m2 m−2). As a whole, the generalized linear mixed model (GLMM) confirmed that litter production was directly proportional to stand density or canopy LAI across almost all culm DBH classes. Litter production also had a positive relation with stand density in relation to canopy LAI or the vice versa. In conclusion, managing the canopy structure in a dense stands and closed canopy through thinning practices enhances canopy LAI and culms DBH and hence maximize D. brandisii litter production in the forest floor. Keywords: Canopy, Litterfall, Litter trap, Season, Temperature, Thinning